Icaritin Alleviates Glutamate-Induced Neuronal Damage by Inactivating GluN2B-Containing NMDARs Through the ERK/DAPK1 Pathway - Liu, Song; Liu, Chaoming; Xiong, Lijiao; Xie, Jiali; Huang, Cheng; Pi, Rongbiao; Huang, Zhihua; Li, Liangdong (Frontiers in Neuroscience, 2021)
Excitatory toxicity due to excessive glutamate release is considered as the core pathophysiological mechanism of cerebral ischemia. It is primarily mediated by N-methyL-D-aspartate receptors (NMDARs) on the neuronal membranes. Our previous studies have found that icaritin (ICT) has neuroprotective effects against cerebral ischemia in rats, but the underlying mechanism is unclear. This study aims to investigate the protective effect of ICT on glutamate-induced neuronal injury and uncover its possible molecular mechanism. The excitatory toxicity injury model was created using rat primary cortical neurons with glutamate and glycine treatment. Results showed that ICT has neuroprotective effects in glutamate-treated primary cortical neurons by increasing cell viability while reducing rate of lactate dehydrogenase (LDH) release and apoptosis. Remarkably, ICT rescues the changes in the ERK/DAPK1 signaling pathway after glutamate treatment by raising the expression levels of p-ERK, p-DAPK1 and t-DAPK1. In addition, it also regulates membrane NMDAR function during glutamate-induced injury by decreasing the expression level of GluN2B subunit and enhancing the expression level of GluN2A subunit. As the co-treatment of an ERK-specific inhibitor U0126 with ICT abolishes its beneficial effects to the ERK/DAPK1 pathway, the NMDAR subtypes and neuronal cell survival, ERK is recognized as a crucial mediator in the protective mechanism of ICT. In conclusion, our findings demonstrate that ICT has a neuroprotective effect on neuronal damage induced by glutamate, and its mechanism may be related to inactivating GluN2B-containing NMDAR mediated by the ERK/DAPK1 pathway. This study provides a new clue for the prevention and treatment of clinical ischemic cerebrovascular diseases.